ANALYSIS OF E-LEARNING ACCEPTANCE IN GENERATION Z STIKI INDONESIA DURING THE COVID-19 PANDEMIC - I Gusti Ayu Agung Mas Aristamy; Theresia Hendrawati (Jurnal TAM (Technology Acceptance Model), 2022)
E-Learning has been applied for a long time in Indonesia and other developed and developing countries. However, research by Salloum et.al., said that E-Learning systems in developing countries were partially or completely not adopted; utilization has not been completed and is considered less than a satisfactory level. This refers to the lack of understanding of the factors that influence adoption. One of the latest studies on distance learning during the COVID-19 pandemic said that there were several obstacles experienced by students, and teachers. This study aims to analyze the adoption of E-Learning technology in Generation Z at one of university in Bali during the COVID-19 pandemic. Results of this study indicate that there is a positive impact of computer self-efficacy and accessibility on the perception of the ease with which students use the E-Learning system. The factors of information quality and content quality positively affect the students' perceived ease of use and usefulness of the E-Learning system. It is this perception of the usefulness and ease of use of the E-Learning system that has an increasing impact on students' intentions and attitudes to use the E-Learning system in the future.